Questões raciais na educação: tendências de pesquisas na área e desafios a serem considerados em estudos futuros - Santos, Géssica Aparecida Pereira dos (2024)
The purpose of this research was to map the trends in studies related to the racial theme in education over the last five years and to understand the involved psychosocial effects. The systematic organization of the generated knowledge used the methodology of Integrative Review. The analysis was conducted on a selected set of 53 studies carried out between 2018 and 2022, available in the Digital Library of Theses and Dissertations (BDTD), obtained from the descriptors: "anti-racist education" and "racial diversity"; as well as "racial discrimination" and "education". By making such a selection, it became possible to perceive the intricate and ambivalent nature of racial relations in Brazilian society. The results indicate that research on racial issues in education has been building a solid theoretical framework to elucidate the fundamental concepts of racism in society. This indicates progress in understanding the problem and addressing it. Some trends stand out: the training of teachers to act critically and reflectively on the racial theme in education, the institutional and structural perspective of racism, the approach of an education aimed at the decolonization of the formal curriculum, seeking to reflect the diversity of Brazilian culture, and the discussion of the intersection between race, class, and gender and their impacts on social structures. Additionally, the research emphasizes the implementation and enforcement of legislation and public policies in education focused on the racial theme. Also highlighted are challenges to be considered in future studies, such as the approach to the theme of whiteness, the production of research related to the hidden curriculum, and the approach to the theme in a transversal manner across all disciplines of the school curriculum